Keteladanan dalam Konteks Kepemimpinan Nasional dan Realitas Kemajemukan Bangsa - Ismail, Faisal (Unisia, 2016)
Indonesian constitutes a pluralistic nation and that of society. The pluralities of Indonesian consist of either horisontal or vertical. This nation needs a national leader who has a good qualified, for instance inclusivce and pluralisric leader. The leader does not only reach position of power but also he or she has capability, integrity, visioneer how to manage the pluralistic nation of Indonesia. The power for leader must return to the people in term of intellectuality, prosperous, social justice and peace that in accordace with trusteed by Allah.